Legal Frameworks Regarding Cryptocurrency in Nepal - Adhikari, Raj Kumar (KDCBAR Law Journal, 2025)
The Nepali government has declared all cryptocurrency-related activities illegal due to its exclusive currency issuance authority and stringent foreign exchange regulations. This prohibition is based on robust anti-money laundering laws and the potential applicability of evolving digital legislation. The article also assesses the costs and risks associated with illicit cryptocurrency activities and encompassing severe legal consequences, financial exposure, and cyber security threats. Finally, it explores the paradox of Nepal Rastra Bank’s exploration into a Central Bank Digital Currency (CBDC), suggesting a recognition of digital currency’s future while prioritizing national control and stability. The study concludes by emphasizing the imperative for public adherence to existing prohibitions while acknowledging the long-term trajectory towards digital financial innovation.